Tourism Industry Is The Third Pillar Of The Economy Of Mauritius - Beekarry, Vimla Keemawtee (2003)
Tourism Industry is the third pillar of the economy of Mauritius. Over the years the government has encouraged development focused on the leisure side of tourism, while the business tourism segment has been neglected. This study looks into the development of business tourism in Mauritius. The study seeks to determine the potential that Mauritius has in developing this segment through establishing an international convention centre. The study firstly reviews the importance that the tourism sector plays in the economy of the island and then analyses the extent that business tourism is developed. It also examines the convention industry to determine how feasible it is for Mauritius to have a convention centre. Based on data gathered from different sources, through literatures, questionnaires and interviews, then a conclusion is drawn as to whether Mauritius can develop the business tourism sector further.